2009
DOI: 10.2528/pier09031306
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer System of Lorentz/Drude Type Metamaterials With Dielectric Slabs and Its Application to Electromagnetic Filters

Abstract: Abstract-In this work, frequency behavior of the multilayer structure comprised of double-negative (DNG) and dielectric slabs is presented in detail. The multilayer structure consists of N pieces DNG and dielectric slabs with different material properties and thicknesses. The incident electric field is assumed to be a monochromatic plane wave with any arbitrary polarization. The DNG layers are realized using the parameters of Lorentz/Drude type metamaterials. Transfer matrix method is used in the analysis to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 114 publications
(60 citation statements)
references
References 30 publications
(33 reference statements)
0
59
0
Order By: Relevance
“…Recent studies show that MTMs provide improvement in light collection for solar cells [5][6][7]. MTMs are artificial structures [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] and they can be specifically constructed for many desired physical properties and applications which cannot be obtained from the conventional materials such as negative refractive index [24], cloaking [25], super lens [26], absorber [27], and so on. Therefore, MTMs have gained a great deal of interest due to their large applicability in the development of efficient devices.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies show that MTMs provide improvement in light collection for solar cells [5][6][7]. MTMs are artificial structures [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] and they can be specifically constructed for many desired physical properties and applications which cannot be obtained from the conventional materials such as negative refractive index [24], cloaking [25], super lens [26], absorber [27], and so on. Therefore, MTMs have gained a great deal of interest due to their large applicability in the development of efficient devices.…”
Section: Introductionmentioning
confidence: 99%
“…Note that the real part of the complex wave number has to be negative for DNG slab which is a common information known in the literature [15]. The DNG slabs are defined using frequency dispersive Lorenz [12] and Drude [13] models in which they can provide simultaneously negative permittivity and permeability at a certain frequency band. The permittivity and permeability of a DNG slab can be represented by Drude and Lorentz media parameters as [2-5, 12, 13]:…”
Section: Theoretical Analysismentioning
confidence: 99%
“…In the mentioned models, the constitutive parameters can be arranged to be simultaneously negative below the electric and/or magnetic plasma frequency. Accordingly, these models can theoretically be used to designate a metamaterial (MTM) system (including multilayer MTM structure) for creating/realizing new functional devices [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Additionally, the Lorentz and Drude models as MTMs have been utilized in many studies in which one of them is the multilayer MTM system with the application of EM filters [12].…”
Section: Introductionmentioning
confidence: 99%
“…The desired physical properties, such as negative permeability, negative permittivity and negative refractive index, were accomplished with the construction of this class of materials [2][3][4][5][6][7][8]. Smith et al [4] and Shelby et al [9] were reported the successful experimental validation of the first metamaterial which exhibits simultaneous negative permittivity and negative permeability by constructing two-dimensional periodic structure unit cells of SRRs with copper strips.…”
Section: Introductionmentioning
confidence: 99%